The Plant V-ATPase - Seidel, Thorsten (Frontiers in Plant Science, 2022)
The V-ATPase is the dominant proton pump in plant cells. It contributes to the cytosolic pH-homeostasis and, energizes transport processes across endomembranes of the secretory pathway. Iand its localization at the trans Golgi network / early endosomes is essential for vesicle transport, for instance for the delivery of cell wall components. Furthermore, it is crucial for the response to abiotic and biotic stresses. The V-ATPase’s rather complex structure and multiple subunit isoforms enable high structural flexibility with respect to the requirements at different organs, developmental stages and organelles. This complexity further demands a sophisticated assembly machinery and transport routes within the cell, processes, which are still not fully understood. Similar complex is tThe regulation of the V-ATPase, which is target of phosphorylation and redox-modifications, but also involves interactions with regulatory proteins like 14-3-3 proteins and the lipid environment. A regulation via reversible assembly as reported for the yeast and the mammalian enzyme has not be proven in plants, but seems to be absent in autotrophic cells. Addressing the regulation of the V-ATPase is a promising approach to adjust its activity for improved stress resistance or higher crop yield.